2006
DOI: 10.1007/s10461-006-9152-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Medication Adherence among HIV-1 Infected Individuals

Abstract: This longitudinal study examined the impact of drug use and abuse on medication adherence among 150 HIV-infected individuals, 102 who tested urinalysis positive for recent illicit drug use. Medication adherence was tracked over a 6-month period using an electronic monitoring device (MEMS caps). Over the 6-month study drug-positive participants demonstrated significantly worse medication adherence than did drug-negative participants (63 vs. 79%, respectively). Logistic regression revealed that drug use was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
261
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(278 citation statements)
references
References 62 publications
9
261
1
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Alcohol, cocaine, and heroin use have all been shown to significantly increase ART non-adherence in patients living with HIV (PLWH). [12][13][14] A meta-analysis of the association between alcohol use and ART adherence found that alcohol use is associated with a 40-50 % decrease in ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Alcohol, cocaine, and heroin use have all been shown to significantly increase ART non-adherence in patients living with HIV (PLWH). [12][13][14] A meta-analysis of the association between alcohol use and ART adherence found that alcohol use is associated with a 40-50 % decrease in ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…De entre las variables explicativas de la falta de adhesión a la TARGA en esta población el consumo de drogas es la que se erige como una de las barreras más claras para conseguir dicha adhesión (Battaglioli-DeNero, 2007;Hinkin et al, 2007). El tratamiento con sustitutivos opiáceos, como la metadona, ha contribuido a mejorar la supervivencia de la población adicta a drogas por vía parenteral, aunque su efecto protector más que por el efecto propiamente farmacológico esté basado en la posibilidad que brinda de reducir daños (Esteban, Gimeno, Barril, De la Cruz, 2004) además de contribuir junto a otros factores como son la organización y la estrategia del tratamiento a aumentar la retención de los pacientes (Camacho, Gimeno, Linares, Gimeno, 2003).…”
Section: Introductionunclassified
“…This is of particular concern given that morbidity can be worse, disease progression -16-more rapid, and treatment more difficult for HIV co-infected individuals (PHAC, 2007) Hogg et al (1998), Ory andMack (1998), andPalella et al (1998) found that the introduction of highly active antiretroviral therapy (HAART) has substantially reduced HIV/AIDS associated morbidity and mortality (as cited in Hinkin et al, 2007). Palepu et al (2006) reports methadone maintenance therapy (MMT) played a significant role in providing improved health outcomes for this susceptible population.…”
Section: Co-infectionmentioning
confidence: 99%
“…Reback, Larkins, and Shoptaw (2003) suggest that environmental instability induces stimulant abuse (as cited in Hinkin et al, 2007). Callaghan, Tavares, and Lawren (2007) report the high rates of reciprocal movement between on-and off-reserve locations are a critical public health concern.…”
Section: Continuous Substance Abusementioning
confidence: 99%
See 1 more Smart Citation